Ubicool - From Theory to Practice - Alves, Helena (Journal of Tourism, Sustainability and Well-being, 2015)
Recruitment and management of volunteers in non-profit organizations is a fundamental activity in increasing these organizations’ capacity and one that can benefit considerably from applying marketing principles. However, these organizations are found to have difficulty in applying marketing principles due to the lack of capacity in this professional area. This article aims to draw a parallel between theory and practice based on the literature in this field and the case study of CooLabora in its activity of university volunteerism - UBICool. The case study shows that many of the principles suggested by theory are applied in this specific case, although often informally and unplanned, and so recognizing the positive and less positive factors can contribute to future improvement with benefits for the organization, volunteers and society.